Varieties of welfare markets from a street‐level perspective: Comparing long‐term care services in Germany and Israel. (5th October 2022) - Cohen, Nissim; Klenk, Tanja; Davidovitz, Maayan; Cardaun, Sarah
Abstract: How does the marketization of social service provision impact the practices of street‐level bureaucrats (SLBs) towards their clients? To explore this question, we compare the markets for ambulatory long‐term care for the elderly in Germany and Israel, which differ in the latitude of choice offered to clients and the intensity of state regulation. Based on 52 qualitative interviews with SLBs and managers of care providers, our study shows that in both countries, institutional contexts play a significant role in shaping street‐level bureaucracy practices. We found that SLBs and managers in Israel engage in entrepreneurial behavior, whereas their German counterparts adopt administrative practices. By identifying these tendencies as responses to the respective welfare market characteristics, the article makes an important contribution to the field of comparative SLB research and furthers our understanding of the broader implications of the marketization of welfare services.